2001
DOI: 10.1002/1099-0682(200105)2001:5<1097::aid-ejic1097>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Strategies for the Strengthening of Polymer−Metal Interfaces

Abstract: Polymers have been widely used for the protection of metals against corrosion and for improving the performance of structural adhesive joints. In this contribution, the weakness and short‐term durability of these polymer−metal interactions and some common approaches for alleviating this problem are briefly reviewed. Among the existing techniques, electrochemical processes offer the advantage of controlled interfacial reactions. Promising results have been reported by Stratmann et al. and Lécayon et al., who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 79 publications
1
51
0
Order By: Relevance
“…87 Besides the electrochemical polymerization of pyrroles and thiophenes, there has been research efforts in electrografting arcylates and methacrylates from electrodes. 88, 89 Jerome et al showed that it is possible to induce reactivity to surfaces of conducting substrates by electrografting NHSA. 90 The resulting strongly adhering coating can act as a versatile reactive film to anchor a variety of amino functionalized molecules, such as catalysts, proteins or amino end-functionalized polymers.…”
Section: Electrochemical Polymerizationmentioning
confidence: 99%
“…87 Besides the electrochemical polymerization of pyrroles and thiophenes, there has been research efforts in electrografting arcylates and methacrylates from electrodes. 88, 89 Jerome et al showed that it is possible to induce reactivity to surfaces of conducting substrates by electrografting NHSA. 90 The resulting strongly adhering coating can act as a versatile reactive film to anchor a variety of amino functionalized molecules, such as catalysts, proteins or amino end-functionalized polymers.…”
Section: Electrochemical Polymerizationmentioning
confidence: 99%
“…Indeed, the deposition of a grafted polymer coating in a solvent for this polymer is not a nucleation-and-growth process: the chains while growing are solvated and thus must be fairly extended. We have shown that in DMF the grains' size increases with the monomer concentration to a greater extent than it is the case in ACN [22]. Thus, in contrast to what happens when films are prepared in 5 ACN, aggregation does come into play when the polymerization is already over, i.e., during precipitation of the non-grafted ends of the chains onto the surface upon washing with a non-solvent of the polymer (washing by DMF followed by ACN, see Exptl.…”
Section: Resultsmentioning
confidence: 77%
“…The complex refractive index of nickel was fixed at 2.11 + i 3.94 [17]. The refractive index for PAN [17] and PEA was 1.91 and 1.47, respectively [22].…”
Section: Characterizationmentioning
confidence: 99%
“…Electrochemically induced polymerization is a particularly flexible and simple way to produce hydrogel coatings [17][18][19][20][21][22]. Polymerization is triggered by the decomposition of an electro-active initiator at the cathode.…”
Section: Introductionmentioning
confidence: 99%